2011
DOI: 10.1242/dev.060194
|View full text |Cite
|
Sign up to set email alerts
|

A LIM-homeobox gene is required for differentiation of Wnt-expressing cells at the posterior end of the planarian body

Abstract: SUMMARYPlanarians have high regenerative ability, which is dependent on pluripotent adult somatic stem cells called neoblasts. Recently, canonical Wnt/-catenin signaling was shown to be required for posterior specification, and Hedgehog signaling was shown to control anterior-posterior polarity via activation of the Djwnt1/P-1 gene at the posterior end of planarians. Thus, various signaling molecules play an important role in planarian stem cell regulation. However, the molecular mechanisms directly involved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
85
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(97 citation statements)
references
References 63 publications
11
85
1
Order By: Relevance
“…This observation supports the hypothesis that the wnt1 ligand, secreted by the newly formed posterior organizer, is the morphogen that sustains nuclear translocation of β-CATENIN-1 at the posterior pole during regeneration (Adell et al, 2009;Petersen and Reddien, 2009b). Later on, the nested expression of the other posterior Wnt ligands would control the re-establishment and maintenance of the gradient (Hayashi et al, 2011;Lander and Petersen, 2016;März et al, 2013;Scimone et al, 2016;Sureda-Gómez et al, 2015) (Fig. 6A).…”
Section: A Gradient Of β-Catenin-1 Along the Ap Axissupporting
confidence: 77%
“…This observation supports the hypothesis that the wnt1 ligand, secreted by the newly formed posterior organizer, is the morphogen that sustains nuclear translocation of β-CATENIN-1 at the posterior pole during regeneration (Adell et al, 2009;Petersen and Reddien, 2009b). Later on, the nested expression of the other posterior Wnt ligands would control the re-establishment and maintenance of the gradient (Hayashi et al, 2011;Lander and Petersen, 2016;März et al, 2013;Scimone et al, 2016;Sureda-Gómez et al, 2015) (Fig. 6A).…”
Section: A Gradient Of β-Catenin-1 Along the Ap Axissupporting
confidence: 77%
“…Anterior and posterior poles are small clusters of cells at the head and tail tip, respectively, and are required for normal planarian head and tail regeneration and PCG expression (Felix and Aboobaker, 2010;Hayashi et al, 2011;Blassberg et al, 2013;Chen et al, 2013;Scimone et al, 2014b;Vásquez-Doorman and Petersen, 2014;Vogg et al, 2014). However, in contrast to teashirt RNAi, inhibition of either anterior or posterior pole formation does not cause a reversal of the head-tail regeneration choice.…”
Section: Discussion Teashirt and The Head-versus-tail Regeneration Dementioning
confidence: 99%
“…This early wnt1 expression is required for stem cells at the posterior wound site to differentiate to form a Wnt gene-expressing pole in the regenerating blastema (Petersen and Reddien, 2009b). Active Hh signalling is required for early wound-induced Wnt gene expression and a number of other genes have now been shown to be required for the formation of the stem cell-dependent phase of later Wnt gene expression (Blassberg et al, 2013;Chen et al, 2013;Currie and Pearson, 2013;Hayashi et al, 2011;Marz et al, 2013;Rink et al, 2009;Yazawa et al, 2009). In junl-1(RNAi) worms, the early phase of wound-induced wnt1 expression was not affected and was equivalent to that observed for control animals at both anterior and posterior wounds ( Fig.…”
Section: Jnk Signalling Is Required For the Stem Cell-dependent Phasementioning
confidence: 99%
“…In particular, Smed-islet (Hayashi et al, 2011), Smed-pitx (Currie and Pearson, 2013;Marz et al, 2013) and Smed-pbx (Blassberg et al, 2013;Chen et al, 2013) have all been shown to be required for correct posterior regeneration. In all cases these genes are necessary for the stem celldependent phase of wnt1 expression and the subsequent activation of Smed-wnt11-2 and Smed-wnt11-5.…”
Section: Jnk Signalling Is Required For the Stem Cell-dependent Phasementioning
confidence: 99%
See 1 more Smart Citation